Where is the happy transit rider? Evaluating satisfaction with regional rail service using a spatial segmentation approach. (August 2018) - Grisé, Emily; El-Geneidy, Ahmed
Abstract: Public transit agencies are delivering transport services in a rapidly changing and highly competitive transportation market. Ensuring rider's satisfaction in such an environment has led several public transit agencies to adopt different marketing strategies. For example, market segmentation analyses are commonly employed by transit agencies to identify groups of users, which are subsequently used as a base for developing policies and strategies aimed at improving customer satisfaction. However, previous studies adopting this market segmentation approach have predominantly ignored spatial and contextual factors related to the transit network and the built environment of where a user resides, resulting in network-wide policies that are difficult to implement especially for agencies with scarce resources. This study presents a new segmentation approach that incorporates spatial and contextual factors in addition to other rider's preferences and satisfaction levels with commuter rail service in the Greater Toronto and Hamilton Area, Canada. Including these factors in a market segmentation analysis has enabled us to recommend service interventions at a local and finer scale compared to previous studies, while at the same time providing the greatest impact on a specified segment of riders. This research provides transit planners and policy makers with a spatial segmentation approach, which can be used to maximize the benefits of service improvements intended to increase satisfaction with public transit among certain groups of users in a region.